2017
DOI: 10.1097/tp.0000000000001238
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Deceased Donor Kidney Discard in the United States

Abstract: We have characterized several important predictors of deceased donor kidney discard. Better understanding of factors that lead to increased deceased donor kidney discard can allow for targeted interventions to reduce discard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 24 publications
1
77
2
Order By: Relevance
“…For example, the NLP model highlights specific types of PHS risk (ie, intravenous drug use) associated with discard. This finding is aligned with research on kidney offer declines in addition to the similar factors, hypertension, diabetes, and insulin use used in previous models . Having a directional understanding of these nuanced associations, in relation to PHS risk, is important given that the Centers for Disease Control and Prevention (CDC) is reevaluating PHS risk definitions…”
Section: Discussionsupporting
confidence: 54%
“…For example, the NLP model highlights specific types of PHS risk (ie, intravenous drug use) associated with discard. This finding is aligned with research on kidney offer declines in addition to the similar factors, hypertension, diabetes, and insulin use used in previous models . Having a directional understanding of these nuanced associations, in relation to PHS risk, is important given that the Centers for Disease Control and Prevention (CDC) is reevaluating PHS risk definitions…”
Section: Discussionsupporting
confidence: 54%
“…Marrero et al . , using data from a more recent era (2000–2012), similarly found that a terminal creatinine >1.5 mg/dl was associated with an increase in the risk of discard (OR 4.31). During the period studied in our analysis, 2399 donors with AKI had both kidneys procured but discarded and 699 donors with AKI had one kidney transplanted and one kidney discarded.…”
Section: Discussionmentioning
confidence: 91%
“…Currently, only one-third of patients undergo transplant within 5 years of listing, and many die or become too sick before receiving an organ offer. 7 Among factors that may be associated with increased rates of kidney discard is the decision to perform a procurement biopsy, 8 to assess the "quality" of deceased donor organs, especially those previously classified as from expanded-criteria donors (ECDs). 6 Although the new US kidney allocation system included provisions designed to increase placement of high-risk organs, 3 the high rate of kidney discard persists, thought to reflect both changing donor demographics and transplant program concerns about performance metrics and optimizing outcomes.…”
Section: Introductionmentioning
confidence: 99%